Early Interest in Shakespearean: Original Pronunciation. (May 2013) - Crystal, David
Abstract : Recent interest in Shakespearean phonology in the 2000s, under the heading of 'original pronunciation' (OP), has a history which can be traced back to the mid-nineteenth century. A memorandum by Richard Grant White in 1865 was followed by a detailed analysis by Alexander Ellis, particular attention being paid to Shakespeare's rhymes. Later studies, transcriptions, or presentations include those of Wilhelm Viëtor, Daniel Jones (whose influence was particularly important), Harold Palmer, F. G. Blandford, and A. C. Gimson. BBC broadcasts of extracts from Shakespeare in OP took place during the 1930s and 1940s, and proved popular, but full productions in London and Cambridge during the 1950s received mixed reviews. Dramaturgical and scholarly criticisms are briefly discussed, and the value of the reconstruction exercise strongly affirmed.